Korean Patient-Perceived Satisfaction Scale of Community-Based Case Management Services (Korean-PSCCM): Development and Psychometric Evaluation. Issue 1 (2nd January 2017) - Park, Claire Su-Yeon; Yoon, Saunjoo L.; Yun, Soon-Nyung; Park, Eunok
ABSTRACT: This study aimed to develop and psychometrically test an instrument for measuring patient-perceived satisfaction with community-based case management services in Korea. The study was conducted in 4 phases: Phase I, development of the instrument; Phase II, pilot testing of the instrument; Phase III, a large-scale study to test reliability and validity; and Phase IV, conversion of the new instrument from Korean to English. The new instrument was determined to have six factors—advocacy of case manager, outcome of care, communication skills, practice of a healthy lifestyle, referral, and recognition of risk factors—and also shown to be reliable.